A New Species of Megalichthys (Sarcopterygii, Megalichthyidae) from the Upper Devonian (Famennian) of Pennsylvania, U.S.A., and a Report on the Cosmine-Covered Osteolepiform Fossils of the Catskill Formation. Issue 2 (3rd March 2020) - Downs, Jason P.; Daeschler, Edward B.
ABSTRACT: New material from the Upper Devonian (Famennian) Catskill Formation of Pennsylvania, U.S.A., indicates the presence of a new species of Megalichthys . A large collection of complete and well-preserved fossil material from the Red Hill field locality enables a thorough anatomical description that is not commonly available in Megalichthyidae. The cranial material includes skull roof, partial cheek, lower jaw, opercular-gular elements, palatoquadrate, and dermal palatal elements. The postcranial material includes pectoral fin elements including cleithrum, mesomeres, and lepidotrichia; pelvic fin including lepidotrichia; and body scales in articulation. The new species is distinguished from other species of Megalichthys by the presence of a pineal series of bones, a triangular-shaped principal gular, and a lack of sensory canal pores on the postparietal. We review the taxonomic history and status of Megalichthyidae and Megalichthys and provide revised diagnoses for each that include only discrete features demonstrated to be sufficient for taxonomic assignment. We discuss additional cosmine-covered osteolepiform fossils from other Catskill Formation exposures. These include the type and only specimen of Sterropterygion brandei and seven new specimens (including a partial snout, a partial parietal shield, a partial postparietal shield, a partial cheek, and complete lower jaws) that potentially represent megalichthyid species in addition to the one at the focus of this study. With this description of new megalichthyid material, the Catskill Formation continues to produce, in some cases, the only known Devonian occurrence of otherwise younger taxa.